Effectiveness of Behavioral Counseling Model of Modeling Techniques for Developing Self Exhibition - Putra, Gusti Agung aditya Nata; Dharsana, I Ketut; Darmayanti, Ari (Bisma The Journal of Counseling, 2017)
This research conducted at SMA LAB Undiksha Singaraja. The type that is "experimental" research with the research design is Group yaitu Control Group Pretes-Postest Group. This study aims to determine the effectiveness of modeling model of behavioral counseling model through lesson study in developing "self exhibition" of students in the eleventh grade of social class at SMA Lab Undiksha Singaraja. The dependent variable in this research is Self Exhibition, while the independent variable is behavioral cognitive counseling with self management strategy by considering the moderator variable in the form of the birth order of the students. This study uses data collection methods such as observation, questionnaires, interviews and diaries. The results of this study are students of the eleventh grade of social class at SMA Lab Undiksha Singaraja, showing symptoms of low self-exhibition and behavioral counseling model using modeling techniques have proven effective in developing self-exhibition students.